'The living death of Alzheimer's' versus 'Take a walk to keep dementia at bay': representations of dementia in print media and carer discourse - Elizabeth Peel (2014)
Understanding dementia is a pressing social challenge. This article draws on the ‘Dementia talking: care conversation and communication’ project which aims to understand how talk about, and to people living with dementia is constructed. In this article I draw on the construction of dementia manifest in two data sets – a corpus of 350 recent UK national newspaper articles and qualitative data derived from in-depth interviews with informal carers. These data were analysed using a thematic discursive approach. A ‘panic-blame’ framework was evident in much of the print media coverage. Dementia was represented in catastrophic terms as a ‘tsunami’ and ‘worse than death’, juxtaposed with coverage of individualistic behavioural change and lifestyle recommendations to ‘stave off’ the condition. Contrary to this media discourse, in carers’ talk there was scant use of hyperbolic metaphor or reference to individual responsibility for dementia, and any corresponding blame and accountability. I argue that the presence of individualistic dementia ‘preventative’ behaviour in media discourse is problematic, especially in comparison to other more ‘controllable’ and treatable chronic conditions. Engagement with, and critique of, the nascent panic-blame cultural context may be fruitful in enhancing positive social change for people diagnosed with dementia and their carers.